ANALYZING THE INFLUENCE OF E-SERVICE QUALITY AND PRODUCT QUALITY ON CUSTOMER SATISFACTION OF E-COMMERCE WEBSITE ZALORA INDONESIA: TESTING PURCHASE DECISION AS THE MEDIATING VARIABLE - Hadi Kusuma Sunyoto; Jennifer Vincentia; Vincent Nathanael (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
The growing number of internet users around the world, particularly in Indonesia is changing the business environment digitally. It leads to the growing numbers of e-commerce which eliminates the distance barrier in doing transactions. The number of online sellers and buyers in Indonesia is also growing as a result from this phenomenon. This research examines the factors that influence customer satisfaction Zalora Indonesia e-commerce, specifically, e-service quality, product quality, and purchase decision. The method of this study is disseminating questionnaires to the respondents as many as 128 who are connected to the internet, also have installed and purchased Zalora Indonesia platforms before. The result of this study shows that e-service quality and product quality significantly influence purchase decision and customer satisfaction. Also, purchase decision significantly influences customer satisfaction. Keywords: e-service quality, product quality, purchase decision, customer satisfaction